Modified Smith predictor‐based optimal fractional PD‐PD controller for double integrating processes with considerable time delay. Issue 2 (29th December 2022) - Sengupta, Sayani; Karan, Somak; Dey, Chanchal
Abstract: Modified Smith predictor (MSP)‐based fractional propotional derivative (PD)‐PD controller (FO [PD‐PD]) is presented here for controlling double integrating plus time delay (DIPTD) processes. The proposed scheme comprises of two fractional PD controllers together and a first‐order filter to ascertain satisfactory servo as well as regulatory responses. Here, forward path fractional PD controller works towards attaining improved servo response and feedback path fractional PD controller ensures enhanced load regulation. Tuning parameters of both the controllers are obtained through optimization algorithm. The first‐order filter present in the feedback path is responsible for providing improved robustness and is designed with single tuning parameter—closed‐loop time constant ( λ ). Efficacy of the proposed MSP‐based fractional order PD‐PD controller or MSP‐FO (PD‐PD) is substantiated through simulation study, and its superiority is established in comparison with others' recent works on DIPTD processes.